Intralesional Mumps, Measles, Rubella (MMR) Vaccine as Therapy for Recurrent Condyloma Acuminata: A Case Report - Sambodo, Shelly Lavenia; Prasetyadi Mawardi; Endra Yustin Ellistasari; Ammarilis Murastami (HM Publisher, 2024)
Background: Condyloma acuminata (CA), a prevalent sexually transmitted infection caused by the human papillomavirus (HPV), presents challenges in treatment due to its high recurrence rate. While various treatment modalities exist, intralesional immunotherapy with the mumps, measles, rubella (MMR) vaccine has shown promise in managing HPV-related conditions. This case report investigates intralesional MMR vaccine in treating recurrent CA. Case presentation: A 24-year-old female presented with recurrent CA lesions on the labia majora and perianal region. Despite prior treatment with trichloroacetic acid (TCA), the lesions had reappeared. Intralesional MMR vaccine injections were administered twice, one month apart, resulting in complete lesion resolution within six weeks of the second injection. No recurrence was observed during a six-month follow-up period, and the patient reported only mild, transient pain at the injection sites. Conclusion: This case report highlights the potential of intralesional MMR vaccine as an effective and well-tolerated treatment option for recurrent CA. Further research is warranted to validate these findings and establish optimal treatment protocols.